Upaya Meningkatkan Minat Siswa SD Terhadap Extra Kurikuler Musik Melalui Implementasi Model Learning by Doing : Penelitian Tindakan Kelas - Tomy Agung Sugito; Marda Putra Mahendra; Izzati Elvira Subianto; Arya Asna Lubbis (SCHOLASTICA JOURNAL JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2024)
The initial interest of elementary school students towards extracurricular music shows a low percentage, which is 50.29%. Therefore, teachers need to make efforts to increase students' interest in that extracurricular music. The learning by doing method is applied to students to enhance their interest in extracurricular music. The methods used are qualitative descriptive and quantitative descriptive (mixing method). Data collection is conducted through questionnaires, observations, interviews, and documentation. The research results indicate that the learning by doing model can increase students' interest in extracurricular music by 90.73% and can foster student interest in the learning process as well as in music activities. In this effort, support from the school and teachers' facilities and infrastructure is needed, including increasing music activities (practice) in the process of learning music arts and requiring students to actively participate in the learning process such as asking questions, giving opinions, and engaging in music activities in the classroom.